Liver Lobe Torsion Following an Enterotomy for an Obstructive Foreign Body in a Puppy - Elizabeth C. Waskover; Jennifer Truong; Lindsay Phillips (Veterinary Medicine and Science)
ABSTRACT A 6‐month‐old male intact Bernese Mountain Dog presented for lethargy and acute vomiting after known foreign body ingestion. The patient was diagnosed with an obstructive foreign body and underwent an exploratory laparotomy with an enterotomy. Twelve hours postoperative, he was diagnosed with a haemoabdomen. A second exploratory laparotomy was performed, and a left lateral and left medial liver lobe torsion was diagnosed. A left lateral liver lobectomy was performed. The left lateral liver lobe was submitted for histopathology and was consistent with acute torsion. This draws interest to the case as the patient is a juvenile dog and there was involvement of two liver lobes which is rare. The cause of liver lobe torsion is unknown in this case. Liver lobe torsion is rare and has never been reported in a young dog as an immediate postoperative complication.